Effect of electron beam radiation on water absorption of hybrid kenaf-glass unsaturated polyester composite - Maleque, Md. Abdul; Afdzaluddin, Atiqah; Mohammad Ismail, Mohammad Abul Fazal; Iqbal, M. M.; Paruka, Perowansa (Trans Tech Publications, Switzerland, 2015)
This paper presents the effect of electron beam radiation on water absorption of kenaf-glass (KG) mat reinforced unsaturated polyester (UPE) hybrid composite which has been compounded using sheet molding compound (SMC) process. Hybrid synthetic and natural fiber composite materials are attractive structural materials because of natural fibers resource and their lower cost making their study a relevant research area today. In the present study, the fabricated hybrid composites were subjected to a dose of electron beam radiation of 75 kGy. Furthermore, fourier transform infra-red (FTIR) analysis was carried out on irradiated hybrid kenaf-glass reinforced UPE composite. It was found that the effect of electron beam radiation increases the impact strength and water uptake significantly.Water absorption values were found to be increased with the increasing of kenaf fiber loading for non-irradiated hybrid KG-UPE composite.